The Lowe syndrome in a 16 years old patient – case report - Mazur-Michałek, Iwona; Gotz-Więckowska, Anna; Kocięcki, Jarosław (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
The Lowe syndrome is a rare genetic disorder. It is inherited in an X–linked recessive manner. The clinical symptoms occur in eyes, central nervous system and kidneys. We describe the case of 16 years old boy with Lowe syndrome who underwent the bilateral congenital cataract surgery at the age of 14 months. The clinical symptoms of patient’s mother are also described.